2010
DOI: 10.1111/j.1467-9507.2009.00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Friendship and Delinquency: Selection and Influence Processes in Early Adolescence

Abstract: Positive association of relevant characteristics is a widespread pattern among adolescent friends. A positive association may be caused by the selection of similar others as friends and by the deselection of dissimilar ones, but also by influence processes where friends adjust their behavior to each other. Social control theory argues that adolescents select each other as friends based on delinquency. Differential association theory, on the other hand, argues that adolescent friends influence each other's deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
2
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(126 citation statements)
references
References 47 publications
6
112
2
6
Order By: Relevance
“…We found that higher levels of peer influence were associated with lower levels of initial gang involvement, a finding contrary to previous research that has found that increased time spent with delinquent peers not only increased the likelihood of engaging in delinquent acts (Keijsers et al, 2012) but also increased the likelihood of gang involvement (Howell & Egley, 2005). Further, delinquent children tend to seek out others who engage in delinquent acts (Knecht et al, 2010). We suspect that youths who are less involved in gangs perceive greater pressure from their peers to become involved.…”
Section: Initial Gang Involvementcontrasting
confidence: 57%
See 1 more Smart Citation
“…We found that higher levels of peer influence were associated with lower levels of initial gang involvement, a finding contrary to previous research that has found that increased time spent with delinquent peers not only increased the likelihood of engaging in delinquent acts (Keijsers et al, 2012) but also increased the likelihood of gang involvement (Howell & Egley, 2005). Further, delinquent children tend to seek out others who engage in delinquent acts (Knecht et al, 2010). We suspect that youths who are less involved in gangs perceive greater pressure from their peers to become involved.…”
Section: Initial Gang Involvementcontrasting
confidence: 57%
“…Youth are at greater risk of gang involvement when other youths in the community are already in a gang (Hill et al, 1999). Increased time spent with delinquent peers increases an individual's chances of engaging in delinquent acts (Jennings, Maldonado-Molina, & Komro, 2010;Keijsers et al, 2012), and delinquent children tend to seek others who also engage in delinquent acts (Knecht, Snijders, Baerveldt, Steglich, & Raub, 2010). A predisposition to delinquent activity also increases the likelihood of gang involvement and violent delinquency (Gordon et al, 2004).…”
Section: Peer Relationshipsmentioning
confidence: 99%
“…Of course, selection effects might play a role here as well. Instead of influencing each other, adolescents might select similar adolescents to socialize with, based on the level of self-control, attitudes or delinquent behavior (Chapple 2005;Knecht et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the false consensus effect may artificially inflate the similarity that an individual perceives between his/her behavior and that of his/her associates. Thus, while studies using direct peer reports continue to yield equivocal evidence concerning whether socialization or selection better accounts for the correlation between personal and peer behavior (e.g., Kandel, 1978;Knecht et al, 2010, Weerman, 2011, they have simultaneously led some to conclude that "estimates of influence [i.e., socialization] are grossly overstated in analyses relying upon respondents' perceptions of their friends' behavior" (Aseltine, 1995:103; see also Haynie, 2001;Kandel, 1996;Meldrum et al, 2009;Weerman and Smeenk, 2005).…”
Section: Implications For Understanding and Controlling Juvenile Crimmentioning
confidence: 99%